2008
DOI: 10.1111/j.1752-7325.2008.00093.x
|View full text |Cite
|
Sign up to set email alerts
|

Is the Child Oral Health Quality of Life Questionnaire Sensitive to Change in the Context of Orthodontic Treatment? A Brief Communication

Abstract: The results provide preliminary evidence of the sensitivity to change of the COHQoL questionnaires when used with children receiving orthodontic treatment. However, the study needs to be repeated in different treatment settings and with a larger sample size in order to confirm the utility of the measure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 9 publications
1
30
1
Order By: Relevance
“…From this point of view, the use of this instrument in research and clinical practice (i.e., clinical trials) is valid, because the instrument can offer information for healthcare professionals to better understand the consequences of the treatment on a patient's QoL. It could potentially help clinicians understand the magnitude of the benefits associated with the treatment for TDI (22,25). So, our results can be developed further to help to evaluate other studies with prepost design analyzing the impact of TDI treatment in other populations and help support political actions and research in public health areas.…”
Section: Discussionmentioning
confidence: 99%
“…From this point of view, the use of this instrument in research and clinical practice (i.e., clinical trials) is valid, because the instrument can offer information for healthcare professionals to better understand the consequences of the treatment on a patient's QoL. It could potentially help clinicians understand the magnitude of the benefits associated with the treatment for TDI (22,25). So, our results can be developed further to help to evaluate other studies with prepost design analyzing the impact of TDI treatment in other populations and help support political actions and research in public health areas.…”
Section: Discussionmentioning
confidence: 99%
“…92 There have been a small number of longitudinal studies, all of which have found an improvement in OHQoL following orthodontic treatment. 42,[93][94][95][96] Furthermore, a case controlled study also reported fewer physical, psychological and social impacts on daily performance associated with a malocclusion, in patients that had received Orthodontic treatment, compared to those who had not. 97 There is still a vigorous debate in the research community about the concept of OHQoL, what OHQoL questionnaires measure and how they should be used in the future.…”
Section: Quality Of Lifementioning
confidence: 99%
“…The use of OHRQoL measures in addition to professional indices offers a potentially useful combination [7,12]. OHIP-14 can be used as a potential proxy measure to replace subjective clinical opinions for determining treatment need in youth [13]. …”
Section: Introductionmentioning
confidence: 99%